Robust Adaptive Attitude Stabilization of a Fighter Aircraft in the Presence of Input Constraints - M. Bahmani; T. Binazadeh (Journal of Electrical and Computer Engineering Innovations, 2016)
The problem of attitude stabilization of a fighter aircraft is investigated in this paper. The practical aspects of a real physical system like existence of external disturbance with unknown upper bound and actuator saturation are considered in the process of controller design of this aircraft. In order to design a robust autopilot in the presence of the actuator saturation, the Composite Nonlinear Feedback (CNF) controller along with the Adaptive Integral Sliding Mode (AISM) controllerand the new robust controller that is called AISM-CNF control law is proposed. The CNF part of controller is used for stabilization of the nominal system and also improvement of the transient performance by considering the actuator saturation. The AISM part guarantees robustness against the model uncertainties and/or external disturbances. Since in the proposed approach, the upper bound of the uncertain terms is estimated and therefore there is no need to the prior knowledge of the upper bound of the model uncertainties. Finally, simulation results show the performance of the proposed AISM-CNF controller in term of attitude stabilization of fighter aircraft, robustness, and the good characteristics of the transient responses of the autopilot system in spite of actuator saturation and external disturbance.